2022
DOI: 10.33963/kp.a2022.0163
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnetic resonance in the detection of cardiac involvement in patients with newly diagnosed extracardiac sarcoidosis: Single center experience

Abstract: Background: Sarcoidosis is a systemic inflammatory disease of unknown etiology, which can affect almost any organ. Cardiac involvement determines the prognosis of the affected individuals. Its prevalence in patients with extracardiac sarcoidosis with the absence of cardiac symptoms remains unclear. Cardiac magnetic resonance (CMR) provides excellent diagnostic accuracy in the detection of heart involvement by sarcoidosis. Aim:We sought to determine the prevalence of cardiac sarcoidosis in asymptomatic individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…What becomes crucial is identifying which suspected sarcoidosis patients should undergo CMR. Kysperska et al [12] showed that it is unlikely to detect CS in the asymptomatic population without ECG or echocardiographic abnormalities, supporting the current guideline recommendations. However, we should acknowledge that the authors performed a comprehensive baseline assessment with all conventional tests such as 12-lead ECG, Holter monitoring, and echocardiography, as well as biomarker testing outside the guideline recommendations.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…What becomes crucial is identifying which suspected sarcoidosis patients should undergo CMR. Kysperska et al [12] showed that it is unlikely to detect CS in the asymptomatic population without ECG or echocardiographic abnormalities, supporting the current guideline recommendations. However, we should acknowledge that the authors performed a comprehensive baseline assessment with all conventional tests such as 12-lead ECG, Holter monitoring, and echocardiography, as well as biomarker testing outside the guideline recommendations.…”
mentioning
confidence: 57%
“…In addition, regional wall motion abnormalities appear to be strongly associated with CS, which should be part of the routine echocardiographic assessment [15]. Finally, there was a weak association between elevated angiotensin converting enzyme levels and CS detection in the latest study presented in this issue of the Kardiol Pol [12]. This would raise suspicion as to whether the clinical impression of disease activity should be included in the screening strategy, and it should indicate the performance of CMR as a screening test.…”
mentioning
confidence: 95%
See 1 more Smart Citation